(untitled) (International Journal of Environmental Sciences, 2025)
Aim: The goal of this study was to create a self-emulsifying Cassia tora drug delivery system, which would enhance its dissolution efficiencies, solubility, and bioavailability. Materials and Methods: Cassia tora’s solubility in various types of cosurfactants, oils, and surfactants was determined. A pseudoternary phase diagram was developed using Cremophor EL, Gelucire 44/14 and PEG 400 to identify the optimal region for emulsification. Other factors such as the emulsification time and drug content were also evaluated. Results and Discussion: The optimized formulation of Cassia tora showed various characteristics, such as its small particle size, high solubility, and good optical clarity. In vitro release was also improved with the help of this formulation. Data importing was performed using HPTLC. Conclusion: The study revealed that SEDDS could be a promising method of delivering poorly soluble drugs orally.